Collaging the Posthuman into the Postnatural - Summers, Dennis (Journal of Posthumanism, 2021)
Collage – that somewhat old-fashioned sounding word, revolutionary in the arts in the early 20th century – remains a powerful and omnipresent creative and interpretive strategy throughout all media, and much philosophy, over one-hundred years later. The value of collage theory to a wide range of topics is derived by recognizing literal or figurative gaps and seams between components, and the conceptual contested space between them. Such ideas are useful when considering characteristics of the posthuman and the postnatural. By tracing collage, the posthuman, and postnatural through several topics in the arts and sciences, unexpected commonalities can be found. The (post) human body threads through these topics: a body of irreversible chimerality, interpenetrating and entangling larger physical, psychological, and cultural environments. At that point the line between the posthuman and postnatural becomes murky at best. That ambiguity raises questions of ethics. The perspective found within one particular ethical response is surprisingly resonant with collage.